Новые данные о трофических связях и распространении Eurytoma hypochoeridis (Hymenoptera, Chalcidoidea, Eurytomidae) - Зерова, М.Д.; Клименко, С.И. (Збірник праць Зоологічного музею, 2017)
Впервые для паразитического вида Eurytoma hypochoeridis Claridge, 1960 выявлен новый хозяин – Eurytoma campanulae Zerova, 1978. Установлено, что E. hypochoeridis паразитирует не только в галлах орехотворок, но и в стеблях колокольчиковых (Campanulaceae) на личинках растительноядного вида – Eurytoma campanulae, не вызывающих образование галлов. Вперше виявлено нового господаря — Eurytoma campanulae Zer. для паразитичного виду з роду Eurytoma — E. hypochoeridis Clar. На відміну від попередніх даних (Claridge, Askew, 1960; Зерова, 1995, 2010) E. hypochoeridis паразитує не тільки в галах горіхотворок, але й в стеблах дзвоникових (Campanulaceae) на личинках рослиноїдного виду — E. campanulae, який не індукує розвиток галів. For the parasitoid species — Eurytoma hypochoeridis Clar. established the new host — Eurytoma campanulae Zer. for the first time. Unlike of previous data (Claridge, Askew, 1960; Zerova, 1995; 2010) E. hypochoeridis is a parasite not only in galls of many species of Cynipidae from genus Aulacidea on herbaceous plants of genus Hypochoeris, Acroptilon, Hieracium, and Cynipidae of genus Phanacis in the stems of Centaurea spp., but also in stems of Campanulaceae infested by larves of Eurytoma campanulae.